2003
DOI: 10.1001/archinte.163.5.525
|View full text |Cite
|
Sign up to set email alerts
|

Management of High Blood Pressure in African Americans<subtitle>Consensus Statement of the Hypertension in African Americans Working Group of the International Society on Hypertension in Blacks</subtitle>

Abstract: T he purpose of this consensus statement is to offer primary care providers (including physicians, nurse practitioners, and physician assistants) a practical, evidence-based clinical tool for achieving blood pressure goals in African American patients. The need for specific recommendations for African Americans is highlighted by compelling evidence of a higher prevalence of hypertension and poorer cardiovascular and renal outcomes in this group than in white Americans. African Americans have disturbingly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
329
2
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(349 citation statements)
references
References 135 publications
11
329
2
7
Order By: Relevance
“…The increased prescription of ACE-inhibitor/ARBs in African Americans is reassuring since these patients are at higher risk for diabetes-related end-stage renal disease, which can be significantly delayed by treatment with ACE-inhibitors/ARBs. Despite earlier studies that suggested that African-Americans did not achieve the same degree of blood pressure lowering with ACE-inhibitor monotherapy as did Caucasian patients (Douglas et al, 2003), guidelines available at the time of this study for the treatment of hypertension in African-Americans (Douglas et al, 2003) considered ACE-inhibitors/ARBs first-line treatments. It is reassuring that our findings suggest that prescribers were aware of these guidelines.…”
Section: Discussionmentioning
confidence: 71%
“…The increased prescription of ACE-inhibitor/ARBs in African Americans is reassuring since these patients are at higher risk for diabetes-related end-stage renal disease, which can be significantly delayed by treatment with ACE-inhibitors/ARBs. Despite earlier studies that suggested that African-Americans did not achieve the same degree of blood pressure lowering with ACE-inhibitor monotherapy as did Caucasian patients (Douglas et al, 2003), guidelines available at the time of this study for the treatment of hypertension in African-Americans (Douglas et al, 2003) considered ACE-inhibitors/ARBs first-line treatments. It is reassuring that our findings suggest that prescribers were aware of these guidelines.…”
Section: Discussionmentioning
confidence: 71%
“…Two important low (or no)-cost preventive measures are first, a reduction in dietary salt intake (13), and second, a greater awareness of the implications of obesity (42). There is good evidence that a reduction in salt intake reduces blood pressure and that black people are more sensitive than white people in this regard (43).…”
Section: Different Focus In Preventive Strategiesmentioning
confidence: 99%
“…With respect to treatment of black hypertensive patients, who are, usually, resistant to monotherapy with ARBs or ACEIs because they are low renin hypertensives, 87 the addition of a diuretic to an ARB or ACEI, eliminates this difference and black patients respond to these regimens similarly to whites. 88 Hypertensive patients with type II diabetes mellitus and diabetic nephropathy should preferably be treated with ARBs according to the recommendations of the American Diabetes Association. 89 However, post-MI patients complicated with heart failure or left ventricular systolic dysfunction should preferably be treated with ACEIs, except for those who are ACEI intolerant.…”
Section: Heart Failurementioning
confidence: 99%